2021
DOI: 10.3389/fnagi.2020.578071
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use on Incident Dementia and Mild Cognitive Decline: A Systematic Review and Meta-Analysis

Abstract: Background: More people with cognitive dysfunction and dementia also fall into the category of high vascular risk, for which aspirin is one of the most frequently used drugs. However, previous studies reporting that aspirin buffers against mild cognitive decline (MCI) and dementia remain controversial. We thus conducted an updated systematic review and meta-analysis to evaluate the association of aspirin use with the risk of MCI and dementia in older adults.Methods: Data sources from PubMed, Embase, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 53 publications
(44 reference statements)
0
21
2
Order By: Relevance
“…Aspirin, a non-steroidal anti-inflammatory drug (NSAID), has been suggested both for the prevention of Alzheimer’s disease (AD) [47] and for the treatment of schizophrenia [48], due to the emerging evidence of excessive inflammatory response in the pathophysiology of both schizophrenia [48] and AD [47]. For the prevention of dementia, evidence is insufficient to fully evaluate the effect of aspirin on cognitive decline and risk of dementia [49,50]. Results from clinical trials investigating effects of adding aspirin to standard antipsychotic treatment in schizophrenia are inconclusive [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin, a non-steroidal anti-inflammatory drug (NSAID), has been suggested both for the prevention of Alzheimer’s disease (AD) [47] and for the treatment of schizophrenia [48], due to the emerging evidence of excessive inflammatory response in the pathophysiology of both schizophrenia [48] and AD [47]. For the prevention of dementia, evidence is insufficient to fully evaluate the effect of aspirin on cognitive decline and risk of dementia [49,50]. Results from clinical trials investigating effects of adding aspirin to standard antipsychotic treatment in schizophrenia are inconclusive [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by H. Li et al summarized the literature up to April 2020 and we checked in Pubmed that there were no further studies on LDASA use and dementia outcomes as of August 2021. 7 Overall, a meta-analysis of 8 studies indicated that the use of any dose of ASA did not significantly decrease the risk of developing dementia (pooled relative risk (RR) [95% CI]: 0.94 [0.77 to 1.16]. However, when the authors restricted the meta-analysis to 4 studies with LDASA exposure and the outcome all-cause dementia 39-42 and 2 studies with LDASA exposure and the outcome AD, 40 41 LDASA use showed a protective effect against all-cause dementia (pooled RR [95% CI]: 0.82 [0.71 to 0.96]) and AD (pooled RR [95% CI]: 0.54 [0.33 to 0.89]).…”
Section: Discussionmentioning
confidence: 99%
“…The latest systematic review of randomized controlled trials (RCT) on the topic was also performed by H. Li et al and included two RCTs – both published in 2020. 7 In the RCT by Matsumoto et al 44 , 2,536 diabetes patients (age 30–85 years; median: 65 years) without CVD were randomized into receiving LDASA (81 or 100 mg) and were followed over a median of 11.4 years. A tendency towards reducing all-cause dementia risk was observed, but the result was not statistically significant (HR [95%CI]: 0.82 [0.58 to 1.16]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various COX-2 inhibitors, aspirin has been speculated to enhance memory in ageing population and mitigate neuropathogenesis in various brain diseases. While some correlative studies indicated that the association between aspirin treatment and memory is uncertain, ample scienti c evidence strongly implies that aspirin prevents memory decline in elderly subjects [13,14]. Eventually, recent reports demonstrated that aspirin treatment considerably improves the synaptic plasticity in the cognitive centres of the experimental brains [15].…”
Section: Introductionmentioning
confidence: 99%